2001
DOI: 10.1126/science.1067716
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Daily Locomotor Activity and Sleep by Hypothalamic EGF Receptor Signaling

Abstract: The circadian clock in the suprachiasmatic nucleus (SCN) is thought to drive daily rhythms of behavior by secreting factors that act locally within the hypothalamus. In a systematic screen, we identified transforming growth factor-alpha (TGF-alpha) as a likely SCN inhibitor of locomotion. TGF-alpha is expressed rhythmically in the SCN, and when infused into the third ventricle it reversibly inhibited locomotor activity and disrupted circadian sleep-wake cycles. These actions are mediated by epidermal growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
299
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 480 publications
(307 citation statements)
references
References 36 publications
(32 reference statements)
4
299
1
3
Order By: Relevance
“…45,46 The biology that connects mood symptoms and circadian rhythms is unknown. However, Kramer et al 47 have demonstrated that the actions of transforming growth factor-a, transduced through the EGFR, inhibit locomotor activity on the running wheel in mice and disrupt circadian cycles when infused into the third ventricle. Waved-2 mice are a naturally occurring strain with an EGFR point mutation that reduces kinase activity by more than 80%.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 The biology that connects mood symptoms and circadian rhythms is unknown. However, Kramer et al 47 have demonstrated that the actions of transforming growth factor-a, transduced through the EGFR, inhibit locomotor activity on the running wheel in mice and disrupt circadian cycles when infused into the third ventricle. Waved-2 mice are a naturally occurring strain with an EGFR point mutation that reduces kinase activity by more than 80%.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the photoperiodic differences in fever duration between LD and SD reported here and elsewhere (Bilbo and Nelson, 2002;Bilbo et al, 2002b) may be due in part to entrainment of the circadian rhythm in body temperature. Given that the generation of circadian rhythms in the periphery is driven by the neural and humoral output of the SCN (Silver et al, 1996;Meyer-Bernstein et al, 1999;Kramer et al, 2001), and is almost entirely independent of any reciprocal influence by the pineal gland or melatonin (Sumova and Illnerova, 1996;Prendergast and Freeman, 1999), PINx would be expected to have little effect on photoperiodic differences in the febrile response to LPS if such differences are due solely to circadian factors.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not this signal normally operates in a diffusible manner and/or is released synaptically requires further examination. A second candidate diffusible signal is transforming growth factor-alpha (TGF-alpha) (Kramer et al, 2001). As with PK2, TGF-alpha is expressed rhythmically in the SCN, and its administration inhibits wheel-running behavior.…”
Section: Circadian Output and Orchestration Of Endocrine Function Difmentioning
confidence: 99%